A new compact, wide bandwidth dual‐passband microstrip filter based on dual‐mode stepped‐impedance‐resonators. Issue 12 (14th October 2022) - Moattari, Azita M.; Bijari, Abolfazl; Razavi, Seyed Mohammad
Abstract: In this article, a new compact, wide bandwidth dual‐band bandpass filter (DB‐BPF) with four transmission zeros (TZs) is proposed. A dual‐path configuration is realized by cascading different dual‐mode resonators. The novel dual‐mode resonators are based on stepped impedance resonators (SIRs) that generate the TZs owing to their intrinsic characteristics. The proposed DB‐BPF can fulfill simultaneous independent control of the external and internal‐resonator coupling. The design procedure based on the cascaded dual‐mode resonators and frequency transformation is also introduced. The surface current distributions are simulated to verify the performance of the proposed filter. The measured results show 2.14/4.33 GHz DB‐BPF with 3‐dB fractional bandwidth (FBW) of 0.27/0.15, respectively, which is suitable for WLAN applications. The return and insertion losses of the passband are better than 15/15‐dB and less than 0.8/1.3‐dB, respectively. The overall physical size of the fabricated DB‐BPF is 20.4 mm × 20.4 mm, equivalent to 0.23 λ g  × 0.23 λ g, where λ g is the guided wavelength at 2.14 GHz. The simulation results are in good agreement with the measurement results.